(untitled) (Statistics, Optimization & Information Computing, 2025)
In this paper, a novel image steganography algorithm mshEdgeGrayFT1 is proposed, which combines the mamdani fuzzy inference system (FIS) and the least significant bit (LSB) technique for grayscale images. The proposed algorithm begins by removing the noise from the image using a Gaussian filter and then masking the image. The differences between the pixel intensities of two consecutive columns (diffColumn_i,j) and rows (diffRow_i,j) of the resultant image are taken as input variables. A Mamdani FIS determines the edge pixels where the confidential data can be hidden. The pixels are categorized into black, gray, and white. The LSB technique is then used to hide the confidential data in the identified edge pixels. Based on various evaluation metrics, the experimental results demonstrate that the proposed algorithm mshEdgeGrayFT1 outperforms other methods.